PSYCHOTIC MANIFESTATIONS IN PRIMARY SJÖGREN’S SYNDROME: CLINICAL CHARACTERISTICS AND PATHOPHYSIOLOGICAL INSIGHTS - Inić, Teodora; Deležan, Saša (Sanamed, 2026)
Psychotic manifestations in primary Sjögren’s syndrome (SS) represent a rare but clinically meaningful complication of the disease. The aim of this paper was to analyze the clinical characteristics, potential pathophysiological mechanisms, therapeutic approaches, and outcomes of psychotic symptoms in patients with SS.A narrative review of the available literature was conducted, with particular focus on case reports and small case series describing psychosis in the context of SS.Psychotic manifestations in SS may arise from central nervous system involvement, immune-inflammatory mechanisms, cytokine dysregulation, and neurotransmitter alterations, as well as from corticosteroid therapy. Pro-inflammatory cytokines, particularly interleukin-6, have been linked to dopaminergic dysfunction and the emergence of positive psychotic symptoms. Corticosteroids may induce psychotic episodes depending on dose and duration of treatment. Chronic somatic symptoms, including ocular and oral dryness, pain, and fatigue, may be vulnerable to delusional misinterpretation. In several reported cases, psychotic symptoms improved following immunosuppressive therapy, supporting a potential immune-mediated subtype of psychosis in this population.Psychosis in primary Sjögren’s syndrome likely has a multifactorial etiology. Early recognition of a possible autoimmune basis is essential, as treatment strategies may require immunomodulatory therapy in addition to standard psychiatric management.
Keywords: Sjögren’s syndrome; psychosis; neuroinflammation; cytokines; corticosteroids; autoimmune diseases